Restrictions on trade unionism in Malaysia: a critical study / Chambai Lindong - Lindong, Chambai (Faculty of Law, 1985)
The right of workmen to organise themselves into associations is a basic human right. This has been recognised by the United Nations Organisations. The standards for freedom of association are spel t out in the International Labour Organisation Conventions. In many areas trade Unionism in this country is very much controlled. This paper will attempt at identifying the areas where trade Unionism is being assaulted. By identifying those areas it is hoped that this paper will highlight the need to lift some of the restrictions on trade Unionism in this country. The major source of information for writing this paper was obtained through. library research, while the rest were obtaine<l from interviews and from attending a talk by a prominent trade Union leader. In writing this paper the writer is very much indebt.ed to his Supervisor, Mr Teh Hock Kee and Mr Darby Hashim, his Course Tutor for their invaluable comments and suggestions which have been adopted. A special thank also go to Cik Raja Kamariah bt. Raja Tepap of the School of Engineering who labouriously typed this paper.